Human X chromosome inactivation and reactivation: implications for cell reprogramming and disease. (25th September 2017) - Cantone, Irene; Fisher, Amanda G.
Abstract : X-chromosome inactivation (XCI) is an exemplar of epigenetic regulation that is set up as pluripotent cells differentiate. Once established, XCI is stably propagated, but can be reversed in vivo or by pluripotent reprogramming in vitro . Although reprogramming provides a useful model for inactive X (Xi) reactivation in mouse, the relative instability and heterogeneity of human embryonic stem (ES) cells and induced pluripotent stem cells hampers comparable progress in human. Here we review studies aimed at reactivating the human Xi using different reprogramming strategies. We outline our recent results using mouse ES cells to reprogramme female human fibroblasts by cell–cell fusion. We show that pluripotent reprogramming induces widespread and rapid chromatin remodelling in which the human Xi loses XIST and H3K27m3 enrichment and selected Xi genes become reactivated, ahead of mitotic division. Using RNA sequencing to map the extent of human Xi reactivation, and chromatin-modifying drugs to potentiate reactivation, we outline how this approach could be used to better design strategies to re-express human X-linked loci. As cell fusion induces the expression of human pluripotency genes that represent both the 'primed' and 'naive' states, this approach may also offer a fresh opportunity to segregate human pluripotent states with distinct Xi expression profiles, using single-cell-based approaches. This article is part of the themed issue 'X-chromosome inactivation: a tribute to Mary Lyon'.